Answer:
y = (3 / (x-7)) - 5
Explanation:
The original equation has the asymptotes at x = 0 and y = 0.
We want to translate to the right by 7 units so that the asymptote is at x = 7 and downwards 5 units so that the asymptote is y = -5.
Now, in the first case, to move it to the right, you must subtract 7 from the independent variable (i.e. x)
And in the second case, to move a function down 5 units, subtract 5 units from the entire function.
Applying the above, the new function would be:
y = (3 / (x-7)) - 5